Analisis Perbedaan Kebijakan Pendanaan Dan Dividen Antara Perusahaan Tumbuh Dan Tidak Tumbuh Pada Perusahaan Properti (Studi Kasus Perusahaan Properti Yang Terdaftar Di Bursa Efek Ndonesia Periode 2015-2020) - Siti Laelatul Qodriyah; Risal Rinofah; Agus Dwi Cahya (EBBANK, 2022)
The purpose of this study was to determine (1) differences n funding policies and (2) differences n dividend policy between growing and non-growing companies. This research s classified as quantitative research. The data collection method uses pooled observation. The data analysis technique used a mean difference test and a classical assumption test consisting of a normality test and a homogeneity test. The results of the analysis show that (1) There are differences n funding policies between growing and non-growing companies n property companies listed on the ndonesia Stock Exchange n the 2015-2020 period with tcount = 4.572 with a significant value of 0.000 < 0 ,05. (2) there s a difference n dividends between growing and non-growing companies using the nvestment opportunity set approach to property companies n property companies listed on the ndonesia Stock Exchange for the 2015-2020 period with tcount = 4,588 with a significant value of 0.00 < 0.05. To conclude, there was positive and significant differences n funding policies and dividend policy between growing and non-growing companies n property companies listed on the ndonesia Stock Exchange n the 2015-2020.